PAssive TRaining In elderly patients with Acute myocaRdial infarCtion (PATRIARCH Study): effects on intracardiac hemodynamics and arrhythmias - A. N. Sumin; A. V. Bezdenezhnykh; O. M. Baydina; T. A. Popova; O. P. Khayredinova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of skeletal electromyostimulation (SEMS) on intracardiac hemodynamics and arrhythmia risk in elderly patients with myocardial infarction (MI). Material and methods. The study included 92 MI patients aged >60 years (mean age 71,4±0,6 years), divided into 4 groups: two SEMS groups of patients aged 60-69 years (n=18) and over 70 years (n=30), plus two control groups, aged 60-69 years (n=19) and over 70 years (n=25). In the main groups (MG), SEMS course was started from treatment day 4-5 (2 hours per day, 10 days; “Myorithm-040” device). Before hospital discharge, strength and endurance of leg skeletal muscles, general physical stress tolerability (PST), 24-hour electrocardiography (ECG) monitoring, and echocardiography (EchoCG) parameters were assessed. Results. In MI patients aged over 70 years, SEMS course increased power and endurance of leg muscles and PST, while these effects were absent among patients aged 60-69 years. In the MG, SEMS was associated with reduced mean circadian heart rate (HR), and no adverse changes in intracardiac hemodynamics, comparing to the CG. During veloergometry stress test, PST in elderly patients significantly and directly correlated with leg muscle strength and endurance, and moderately and inversely correlated with age and maximal HR at night. Conclusion. SEMS is a safe method of PST increase in MI patients aged over 70 years. This method should be studied further and implemented into clinical practice.